2011
DOI: 10.1007/s11010-011-0727-3
|View full text |Cite
|
Sign up to set email alerts
|

Impaired miR-146a expression links subclinical inflammation and insulin resistance in Type 2 diabetes

Abstract: Type 2 diabetes patients exhibit subclinical inflammation but the regulatory mechanisms are poorly understood. We sought to evaluate the role of miR-146a expression along with its downstream proinflammatory signals in relation to glycemic control and insulin resistance. Study subjects (n = 20 each) comprised of clinically well characterized Type 2 diabetes patients and control non-diabetic subjects. miRNA and mRNA expression levels were probed in peripheral blood mononuclear cells (PBMC) by Real-time RT-PCR an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
159
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(173 citation statements)
references
References 43 publications
8
159
1
1
Order By: Relevance
“…TNF-α plays an important role in the development and progression of diabetic nephropathy supported by the observation of increases in renal TNF-α levels in diabetic animal models and patients (37,38), indicating that increased TNF-α levels result in renal damage. Clinical studies have reported significant increases in the renal production of IL-1β and IL-6 in patients with type 2 diabetic nephropathy compared with that in diabetic patients without nephropathy, suggesting a role of IL-1β and IL-6 in the pathogenesis of diabetic nephropathy (39,40). Similar to the aforementioned opposing effects of SIRT4 in glucose-induced podocytes, SIRT4 overexpression also attenuated the production of TNF-α, IL-1β and IL-6.…”
mentioning
confidence: 82%
“…TNF-α plays an important role in the development and progression of diabetic nephropathy supported by the observation of increases in renal TNF-α levels in diabetic animal models and patients (37,38), indicating that increased TNF-α levels result in renal damage. Clinical studies have reported significant increases in the renal production of IL-1β and IL-6 in patients with type 2 diabetic nephropathy compared with that in diabetic patients without nephropathy, suggesting a role of IL-1β and IL-6 in the pathogenesis of diabetic nephropathy (39,40). Similar to the aforementioned opposing effects of SIRT4 in glucose-induced podocytes, SIRT4 overexpression also attenuated the production of TNF-α, IL-1β and IL-6.…”
mentioning
confidence: 82%
“…Expression of immune-modulatory miRNAs, especially miR-146a, has been determined in different diabetic complications, [48][49][50][51][52] including DN. 49,[53][54][55] While some studies have shown lower miR-146a expression during DN, 49 others have shown higher expression.…”
Section: Discussionmentioning
confidence: 99%
“…Table 4 Correlation analysis between laboratory parameters and miRNAs in non-alcoholic fatty liver disease patients In one study, the miR-146a expression levels were significantly decreased in peripheral blood mononuclear cells from patients with Type 2 diabetes compared to control subjects. They also reported that reduced miR-146a levels are associated with insulin resistance and poor glycemic control [18] . Although miR-146a and miR-146b are encoded on different chromosomes, their mRNA targets are predicted to overlap significantly [19] .…”
Section: 05) and Further Confirmed By Sam Test (Q < 5%)mentioning
confidence: 99%